Urethral Reconstruction by Full Thickness Abdominal Skin Graft – Our Experience (Bangladesh Journal of Urology, 2022)
Introduction: This study is an effort to develop an alternative to available graft sources for complex and long-segment strictures. For this to assess the outcome of harvesting a full-thickness abdominal skin graft for urethral reconstruction we conducted this study.Material and Method: The study was prospective type of observational study. Data were collected between June 2019 and November 2021 from patients underwent urethroplasty using full thickness skin grafts harvested from abdominal skin.Result: Total 16 patients followed up. Mean stricture length was 8 + 3.38 cm (range 5-12 cm). The aetiology [Figure 2] of urethral stricture included urethritis (6 patients), urethral trauma (7 patients), failed hypospadias repair (2 patient) and unknow (1 patient). The mean prepared graft length was 8.68 + 4.58 cm (range 7–14 cm), the mean operation time was 86.45 + 30.28 minutes (range 55 –130 minutes). Median follow-up was 24 months. 2 patients developed febrile urinary tract infections requiring oral antibiotics. 1 patient with history of urethritis developed recurrent stricture. So overall success rate is 93.75% with p value of < 0.001; that is statistically significant.Conclusion: Selective use of abdominal skin grafts may be well suited for patients with long-segment urethral strictures in one or two stages when other graft sources are not available or feasible.Bangladesh J. Urol. 2021; 24(2): 175-180